Correlates of Lifetime Physical Abuse Among Schoolchildren Aged 15 Years in Post-communist Albania - Gentiana Qirjako; Qamil Dika; Qamil Dika; Iris Mone; Xheladin Draçini; Loreta Kuneshka; Enver Roshi; Genc Burazeri; Genc Burazeri (Frontiers Media S.A., 2021)
Aim: Our aim was to assess the prevalence and correlates of lifetime physical abuse among schoolchildren in Albania, a post-communist country in South Eastern Europe which is currently undergoing a rapid socioeconomic transition.Methods: The third wave of Health Behavior in School-Aged Children (HBSC) in Albania was conducted in 2017-18 including a nationwide representative sample of 1,708 schoolchildren aged 15 years (54% girls; response rate: 95%). Children were asked to report on lifetime physical abuse and a wide range of socio-demographic factors, lifestyle factors and health status characteristics. Binary logistic regression was used to assess the independent association of lifetime physical abuse with covariates.Results: Overall, the prevalence of lifetime physical abuse was about 32% (30% in boys vs. 32% in girls). In multivariable-adjusted logistic regression models, independent positive correlates of lifetime physical abuse among Albanian schoolchildren included lifetime smoking (OR = 1.5, 95% CI = 1.1-2.2), lifetime alcohol consumption (OR = 1.6, 95%CI = 1.2-2.1), irritability (OR[dailyvs.rarely/never] = 2.0, 95%CI = 1.3-3.0), and especially lifetime witnessed domestic violence (OR = 4.2, 95%CI = 2.2-7.9). Conversely, a higher score on life satisfaction was inversely related to lifetime physical abuse (P < 0.01).Conclusion: Our study provides novel evidence about the magnitude and selected independent correlates of lifetime physical abuse among schoolchildren in Albania, a country still embedded in an everlasting transition which is associated with tremendous changes in family structure, community links and societal norms and values. Irrespective of a wide range of sociodemographic factors and health characteristics, lifetime smoking, alcohol consumption, irritability, a lower score on life satisfaction and, particularly, witnessed domestic violence were strong and significant correlates of lifetime physical abuse among Albanian schoolchildren aged 15 years.